Recalibrating the Scales of Municipal Court Justice in Missouri: A Dissenter’s View - Kimberly Jade Norwood (Washington University Journal of Law & Policy, 2016)
This Article examines the inefficiencies of Missouri municipal courts that came into sharp focus following the killing of Michael Brown by Officer Darren Wilson in Ferguson, Missouri. Norwood details and expands on her lone dissent in the Final Report of the Municipal Division Work Group—a group created by the Missouri Supreme Court to address the alleged abuses of black and poor residents in Missouri. Norwood argues for consolidating failing municipal courts to create larger, more functional, and just courts.
Keywords: Municipal courts; Justice; Missouri; Ferguson; Michael Brown; Darren Wilson; ArchCity Defenders; law enforcement; racial relations; Department of Justice; reform